Pancreatic toxicity in mice elicited by Tityus zulianus and Tityus discrepans scorpion venoms - Borges, Adolfo; Trejo, Ernesto; Vargas, Alba Marlene; Céspedes, Ghisleine; Hernández, Alipio; Alfonzo, Marcelo J (Investigación Clínica, 2009)
Envenoming by Tityus discrepans (TD) scorpions in northcentral Venezuela mainly causes pancreatic and gastrointestinal complications whereas the sting by Tityus zulianus (TZ) (western Venezuela) often produces respiratory arrest and death by pulmonary oedema. Since TZ pancreatic toxicity may have been overlooked, a study was carried out to evaluate TZ venom effect on mice pancreas. BALB/c mice were injected intraperitoneally with 0.5 mg protein/kg of either TD or TZ venoms. A significant increase in serum-amylase activity (IU/mL) was obtained after 3 h (20.6 Ó 3.0, p < 0.05) and 6 h (60.4 Ó 3.0, p < 0.001) of TZ venom injection compared to saline-inoculated mice. Increased amylase levels were also elicited by TD venom, although these were significantly lower than those induced by TZ. Light microscopy of pancreas from TZ-envenomed mice revealed interstitial oedema and vacuolization of acinar cells as soon as 1 h after injection. Differences in the time course of the pancreatic oedema (wet pancreas weight/body weight ratio) elicited by TD and TZ venoms suggest the existence of species-specific mechanisms for oedema formation. Taken together, these data suggest that the TZ venom contains components highly toxic to the mammalian pancreas, which may play a role in developing TZ-related pulmonary complications.